Non-conventional indigenous mineral supplements used for cattle feeding in the pastoral rangelands of Ethiopia - Kabaija, E. (Springer, 1989)
A study conducted to assess and sample the composition and quality of native supplements such as salt licks, soil licks and well waters from various parts of Ethiopia used by pastoral nomads for cattle feeding.